The associations between non-suicidal self-injury and first onset suicidal thoughts and behaviors - Kiekens, G.; Hasking, Penelope; Boyes, Mark; Claes, L.; Mortier, P.; Auerbach, R.; Cuijpers, P.; Demyttenaere, K.; Green, J.; Kessler, R.; Myin-Germeys, I.; Nock, M.; et al. (Elsevier BV, 2018)
Background: Theoretical and empirical literature suggests that non-suicidal self-injury (NSSI) is an important correlate of suicide risk. The present study was designed to evaluate: (a) whether NSSI is associated with increased odds of subsequent onsets of suicidal thoughts and behaviors (STB) independent of common mental disorders, (b) whether NSSI is associated with increased risk of transitioning from suicide ideation to attempt, and (c) which NSSI characteristics are associated with STB after NSSI. Method: Using discrete-time survival models, based on retrospective age of onset reports from college students (n = 6,393, 56.8% female), we examined associations of temporally prior NSSI with subsequent STB (i.e., suicide ideation, plan, and attempt) controlling mental disorders (i.e., MDD, Broad Mania, GAD, Panic Disorder, and risk for Alcohol Dependence). NSSI characteristics associated with subsequent STB were examined using logistic regressions. Results: NSSI was associated with increased odds of subsequent suicide ideation (OR = 2.8), plan (OR = 3.0), and attempt (OR = 5.5) in models that controlled for the distribution of mental disorders. Further analyses revealed that NSSI was associated with increased risk of transitioning to a plan among those with ideation, as well as attempt among those with a plan (ORs = 1.7–2.1). Several NSSI characteristics (e.g., automatic positive reinforcement, earlier onset NSSI) were associated with increased odds of experiencing STB. Limitations: Surveys relied on self-report, and thus, there is the potential for recall bias. Conclusions: This study provides support for the conceptualization of NSSI as a risk factor for STB. Investigation of the underlying pathways accounting for these time-ordered associations is an important avenue for future research.